Nebesna sotnia gen. & sp. nov. from Baltic amber supports a Pangean distribution of the amphinotic family Ameletopsidae (Ephemeroptera) - Godunko, Roman J; Martynov, Alexander V; Damzen, Jonas; Staniczek, Arnold H (Scientific reports, 2025)
Extant representatives of the mayfly family Ameletopsidae Edmunds, 1957 as well as other three small families (Nesameletidae Riek, 1973, Oniscigastridae Lameere, 1917 and Rallidentidae Penniket, 1966) traditionally have been classified within the paraphyletic superfamily Siphlonuroidea. Except for Rallidentidae, which are endemic to New Zealand, they have an amphinotic distribution. Ameletopsidae are present with two genera in South America, one genus in Australia, and one genus in New Zealand. The fossil record of Ameletopsidae is scarce. The Mesozoic monospecific genus Promirara Jell & Duncan, 1986 was described from a larva of the Early Cretaceous Koonwarra Fossil Bed in Australia. Also associated with Ameletopsidae is the Cenozoic genus Balticophlebia Demoulin, 1968, which was recorded from Eocene Baltic amber based on a female adult. While the systematic position of the Eocene Balticophlebia seems to be still unclear and in need of clarification, we are able to confirm the presence of Ameletopsidae in the Eocene of Europe by describing Nebesna sotnia gen. & sp. nov. based on a relatively well-preserved male imago from Baltic amber. The fossil record thus indeed supports an ancient Pangean history of this family.
Keywords: Male; Australia; Ephemeroptera; Laurasia; jantar; New Zealand; Animals; zkameněliny; Cenozoic; Mesozoic; Amber; Austrálie; mužské pohlaví; Female; Nový Zéland; Fossils; Mayflies; ženské pohlaví; Siphlonuroidea; zvířata; fylogeneze; Phylogeny; amphinotic distribution; Pangea